If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + -4 = -19 Reorder the terms: -4 + 5u = -19 Solving -4 + 5u = -19 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5u = -19 + 4 Combine like terms: -4 + 4 = 0 0 + 5u = -19 + 4 5u = -19 + 4 Combine like terms: -19 + 4 = -15 5u = -15 Divide each side by '5'. u = -3 Simplifying u = -3
| x+x+1=171 | | x-6y=9 | | x+x+x+1=171 | | .4x-.35x=2 | | 3x-5=5x-15 | | x+x+4=38 | | 9(5d-7)= | | 7x-y=-2 | | -3e+=-23 | | (2x+5)(3x-7)=0 | | 3x+7(x+2)-13=12-3x | | 4(7c+4)= | | 3(x+2)=8+x | | -4(t-4)+6t=5t-1 | | 8x+4x+2+8=7x+3+4X | | -4x+4=-2x+10 | | 3x-3=12x-39 | | 5(h+3)=3(h-5) | | 4x+12=102 | | 2x^2+4=2 | | 6p+30q+42r= | | -8(2b+4)+(17b-7)=0 | | 10a+50b= | | 14-2c= | | 8(a+4)= | | 20b-12= | | 0.5x+2=1.5x+1 | | 10=6-2m | | x+2y=-3 | | 10x-6=7+18 | | -5(t-5)+8t=5t-7 | | 2x+31=10-9 |